Nonoperative management of hemodynamically unstable abdominal trauma patients with angioembolization and resuscitative endovascular balloon occlusion of the aorta. Issue 1 (January 2015) - Ogura, Takayuki; Lefor, Alan T.; Nakano, Minoru; Izawa, Yoshimitsu; Morita, Hideo
<x xml:space="preserve">Abstract</x> BACKGROUND Many hemodynamically stable patients with blunt abdominal solid organ injuries are successfully managed nonoperatively, while unstable patients often require urgent laparotomy. Recently, therapeutic angioembolization has been used in the treatment of intra-abdominal hemorrhage in hemodynamically unstable patients. We undertook this study to review a series of hemodynamically unstable patients with abdominal solid organ injuries managed nonoperatively with angioembolization and resuscitative endovascular balloon occlusion of the aorta. METHODS The institutional review board approved this study. All patients were appropriately resuscitated with transfusions, and angiography was performed after computed tomography. Resuscitative endovascular balloon occlusion of the aorta was performed before computed tomography in all patients. RESULTS Seven patients underwent resuscitative endovascular balloon occlusion of the aorta following severe blunt abdominal trauma. The 28-day survival rate was 86% (6 of 7). There were no complications related to the procedure. CONCLUSION We describe the first clinical series of hemodynamically unstable patients with abdominal solid organ injury treated nonoperatively with angioembolization and resuscitative endovascular balloon occlusion of the aorta. Survival rate was 86%, supporting the need for further study of this modality as an adjunct to the nonoperative management of patients with severe traumatic injuries. LEVEL OF EVIDENCE Therapeutic study, level V.